Influence of fat level and calorie:protein ratio on performance and carcass composition of young pigs - G L Allee; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1972)
One hundred forty pigs averaging 28 pounds were fed a corn-soybean meal diet to study the influence of fat level and calorie:protein (C:P) ratio on the performance and carcass composition. With a constant C:P ratio, fat level made no significant difference on daily gains, but feed efficiency improved as fat level increased. Increasing fat without adjusting the C:P ratio decreased daily gain and metabolizable energy per unit of gain increased. With a constant C:P ratio, feeding 6 or 12% fat did not influence fat content of the carcass. However, feeding 12% added fat without adjusting the C:P ratio markedly increased fat content of the carcass.; Swine Day, Manhattan, KS, November 2, 1972
Keywords: Swine day; 1972; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 193; Swine; Fat; Calorie:Protein ratio; Performance; Carcass composition; Metabolizable